A news frame and care ethics analysis of mental illness in the media: A case study of a South African news website, two international sports stars and mental illness - De Vries, Florence Diana (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.